Economic Potential of Timber Production from Yargey Community Forest under Tsirang District in Bhutan - Gem, Tshering (วารสารวนศาสตร์ไทย, 2022)
A field survey was conducted during the spring of 2010 to study timber production and investigate the financial return of timber sales from Yargey community forest in the Tsirang dzongkhag (district) in Bhutan. In total, 71 respondents were randomly selected for interviews using stratified random sampling by target groups namely, the community forest management group, household furniture/sawmill owners, general timber consumers and contractors. Data were gathered by employing semi structured interviews. Demand and prediction functions were determined and the Durbin-Watson statistical test was employed for testing serial correlation in the demand function. The results showed that demand for timber was dependent on the timber price with an R2 value of 93.73. The timber price coefficient (60.3036) was significant at the 0.01 level. Analysis of the marketing channels of the timber products indicated that 89% was used for domestic consumption and 11% for marketing purposes. The financial analysis revealed a profit of Nu. 151.92/m3 and 1,581.37/m3 from = 7.56 m3 of timber and lumber production, respectively (Nu 44.45 = USD 1). Profit from sale of a sofa set was the highest at Nu. 3931.30. Keywords: economic potential, community forest, Tsirang, Bhutan